Physiological doses of calcium regulatory hormones do not normalize bone cells in uraemic rats - Szabó, A.; Freesmeyer, M. G.; Abendroth, K.; Stein, G.; Rosivall, L.; El-Shakmak, A.; Ritz, Eberhard (European journal of clinical investigation, 1999)
Low bone turnover despite normal parathyroid hormone (PTH) concentrations has been found in many patients with end-stage renal failure. Hyporesponsiveness to the calcaemic action is also a known feature of uraemia. Hyporesponsiveness of bone surface cells involved in bone modelling has not been demonstrated to date. It was the purpose of this study using a rat model of moderate renal failure to investigate whether doses of PTH and calcitriol that reverse the effect of parathyroidectomy on calcaemia also normalize bone surface cell activity.